The genius of Lancelot Biggs - Bond, Nelson S., 1908-2006; Krupa, Julian S., 1913-1989 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Genius of Lancelot Biggs" by Nelson S. Bond is a science fiction novel written in the early 20th century. This engaging narrative features Lancelot Biggs, an eccentric and ingenious character, embarking on an adventure aboard the spaceship "Saturn". The book explores themes of espionage and clever problem-solving within a futuristic space context. The story follows Sparks, the ship's radio operator, who finds himself bunking with the peculiar Lancelot Biggs as they transport contraband to rebels on New California. Their trip is disrupted by the arrival of Mr. Thaxton, a mysterious passenger who turns out to be an esper$1 (Ba person with heightened psychic abilities. As Thaxton threatens to expose their mission, the seemingly bumbling Biggs proves he is anything but ordinary. He uses his knowledge of hypnosis to outwit Thaxton and secure their freedom by manipulating him into believing they carried no contraband. The tale combines humor, clever dialogue, and unexpected twists, showcasing Biggs' unique genius and leaving readers entertained and invested in the characters$1 (Bfates. (This is an automatically generated summary.)s
Release date is 2024-07-23
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Space ships -- Fiction; Psychic ability -- Fiction